Editorial Vol. 13 Issue 1 - Sarah D Asebedo (Journal of Financial Therapy, 2022)
The articles in this issue build our knowledge of the intersection between couples and money by taking us on an evidence-based journey through the beginning (newlyweds and emerging adults) and end (divorce) of a couples’ relationship life cycle while giving insight into early childhood experiences (trauma) that might impact financial beliefs, behaviors, and financial transparency in relationships. These articles incorporate several interesting concepts including adverse childhood experiences, attachment styles, early financial discussions, financial conflict, alimony decisions, spenders, and tightwads. Furthermore, the authors do a fine job of incorporating advanced statistical methods (e.g., structural equation modeling, missing data methods, actor-partner interdependence modelling) to test their research questions, thereby demonstrating the scientific rigor within financial therapy research. There are several broad practice implications within this issue. Enjoy!